Peningkatan Hasil Belajar PAI Dengan Metode Diskusi Pada Siswa Kelas IV SD Negeri 16 Padang Mentinggi - Sriandalia, Sriandalia (EduSpirit : Jurnal Pendidikan Kolaboratif, 2024)
This study aims to improve student learning outcomes in Islamic Religious Education (PAI) for grade IV students at SDN 16 Padang Mentinggi by applying the discussion method. The study was conducted in two cycles, with the first cycle showing the need for further improvement, while the second cycle demonstrated significant improvement. In the first cycle, 68.75% of students achieved learning mastery, while in the second cycle, 100% of students reached mastery. These results indicate that the discussion method, combined with audiovisual media, can enhance students’ understanding of the lesson and motivate them to be more active in class. This research provides evidence that the application of the discussion method is effective in improving learning outcomes and student participation in PAI lessons.